The teacher as designer? What is the role of ‘learning design’ in networked learning? - Konnerup, Ulla; Ryberg, Thomas; Sørensen, Mia Thyrre (Proceedings of the International Conference on Networked Learning, 2018)
This paper explores various strands of ‘Learning Design’ and the understandings of Learning Design that have been developing or are emerging across research fields. We aim to understand the differences and similarities that have developed within various areas, such as Technology Enhanced Learning (TEL), networked learning, designs for learning and draw out their development and branching to understand potentially different ontological or epistemological roots they draw on. Further, we wish to inquire into how the area of ‘Learning Design’ relate to or distances itself from the philosophy and values of networked learning.